Edukasi Pentingnya Peran Suami Dalam Kepatuhan Pemeriksaan ANC Ibu Hamil Di Pulau Pa’jenekang Kabupaten Pangkep - erniawati erni; Sumarni manda; Haerani Rani (JCS, 2022)
Antenatal Care is one of the pillars of safe motherhood in an effort to reduce maternal and fetal morbidity and mortality. To make the program successful, the Indonesian government carries out activities such as antenatal care in improving the health quality of pregnant women. Another program that has been launched by the Government of Indonesia is "Making Pregnancy Safer" where it is expected that the husband's participation, knowledge and involvement can increase during the pregnancy process. But until now there are still many husbands who do not understand their role properly. So it is necessary to make efforts to increase knowledge through counseling about the importance of the husband's role as a facilitator in preparing the process of pregnancy to delivery. Counseling is done using the lecture method using leaflets. Evaluation was carried out before and after the provision of counseling materials. Counseling was carried out for 1 day on Pa'Jenekang Island, Kab. Pangkep became 28 husbands. The results showed that 78.6% experienced an increase in knowledge about the importance of the husband's role as a facilitator while 21.4% had no increase in knowledge. One of the factors that influence the increase in knowledge of the husband's role is age and level of education. Suggestions for health workers should always include husbands in providing KIE in preparation for childbirth by explaining their role in the process of pregnancy and childbirth of the wife.